MEMBUAT ANIMASI BERGERAK MENGIKUTI GERAKAN MANUSIA DENGAN TEKNIK BODY TRACKING - Sukri, Wahyudin (Jurnal Sintaks Logika, 2022)
This research is motivated by the existence of technology that can combine 2 (two) or 3 (three) dimensional virtual objects into a real environment, the technology is augmented reality. in the process of animating or providing motion in 2-dimensional or 3-dimensional animation, special software is needed for its management and skills and experience that are qualified to create a moving animation well. Based on this background, the purpose of this research is to make animations that follow human movements with body tracking techniques. By using quantitative research methods, where this study seeks to describe and interpret objects as they are. The data is obtained indirectly (Study Literature), namely collecting information data related to the research being carried out, such as studying libraries or libraries from Javascript, namely p5.js. This application can track or track objects other than humans such as dolls and human photos. In an article that discusses the research conducted, making this application by running the application there is a delay in animation movement of the object followed by its movement with an average delay of 1.48s with a total of 33 trials and a distance of 15 -500 cm due to VGA and less capable processors.